Influence of pumpkin cellulose on conformational transformations in dough and bread from wheat flour - Shevchenko, Anastasiia; Litvynchuk (Vorontsova), Svitlana; Drobot, Vira; Shevchenko, Oleksandr (My University, 2023)
The aim of the present study was to determine the effect of pumpkin cellulose addition to wheat flour on conformational transformations in the structure of dough and bread. The granulometric composition, functional and technological properties, and amino acid composition of pumpkin cellulose were compared with those of premium grade wheat flour. The influence of pumpkin cellulose in combination with phospholipids on conformational transformations in the structure of dough and bread was studied by method of infrared spectroscopy in the range of near-infrared regions. It was found that 96% of the particles of wheat flour of the premium grade passed through a sieve with holes of 132 microns, the remaining 4% – through a sieve with holes of 260 microns. Pumpkin cellulose was much coarser, because all 100% of its particles remained on a sieve (hole size 670 microns). Moisture binding capacity of pumpkin cellulose was 3.6 times higher, and moisture retaining capacity was 2.8 times higher than of wheat flour due to the presence of a significant amount of fibers. The amino acid score of lysine (the limiting amino acid in wheat flour) was 0.44. The amino acid score of methionine (the limiting amino acid in pumpkin cellulose) was 3.16, and the amino acid score of lysine was much higher than in wheat flour 3.49. Partial replacement of wheat flour with pumpkin cellulose (5–15%) increased this indicator for lysine by 6.5–15.2%. It was found that infrared spectra of dough samples after kneading (control sample and sample with the partially flour replacement by pumpkin cellulose) practically overlapped throughout the range of wavelengths. During the fermentation process conformational changes of functional groups occurred intensively as well as changes in structural and mechanical properties. The dough ball of the control sample thinned faster. Shape-retaining ability improved with increasing replacement percentage of wheat flour with pumpkin cellulose. The partial replacement of wheat flour with pumpkin cellulose enhanced the biological value of bread and changed the structural and mechanical properties improving shape-retaining ability of dough but decreasing dimensional stability of bread.
Keywords: pumpkin; flour; cellulose; bread; dough; spectroscopy; кафедра технології хлібопекарських і кондитерських виробів; кафедра фізики та професійної безпеки; кафедра процесів і апаратів харчових виробництв